Evaluation of Selective Nutritional and Antinutritional Components in Underground Storage Organs - Pillai, S.Chidambaram; Suresh, N.; Padmasree, M. (Asian Journal of Biological and Life Sciences, 2012)
A study on selected nutritional and antinutritional contents in the edible parts of ten domesticated underground storage organs was carried out. Their quantitative data obtained have been depicted and compared with other similar studies in the storage organs of wild nature. Among them, Manihot esculenta, a tuber was found to have highest amount of nutritional contents and is recommended as good dietary source.